Older adults with disability in extreme poverty in Peru: How is their access to health care? - Flores-Flores, Oscar (2018)
Background Disability rates increase with age. In 2012, Peruvian older adults ( 65 years) represented 9% of the population. Additionally, older population reported disabilities at about 5 times the rate of Peruvians between 36 and 64 years old, and 30% of older population lived in poverty. Peruvian seniors living in extreme poverty experience disabilities and the extent of their access to healthcare is unknown. Objective This study assesses associations between disability and access to healthcare among Peruvians older individuals living in extreme poverty. Methods Secondary analysis of a national representative population based survey that utilizes information from Peru’s 2012 survey Health and Wellbeing in Older Adults (ESBAM), which includes older adults living in extreme poverty. We define disability in terms of the Activities of Daily Living (ADL disability) framework. Healthcare access was assessed as having any of Peru’s available health insurance schemes combined with preventive health services (vision assessment, influenza vaccination, blood pressure assessment, diabetes screening, and cholesterol assessment). Poisson robust regression models were used to evaluate the associations among relevant variables. Prevalence Ratios and 95% confidence intervals (95%CI) were reported. Results Data from 3869 individuals (65 to 80 years old), of whom 1760 (45.5%) were females, were analyzed. The prevalence of ADL disability was 17.3% (95%CI: 16.0%-18.4%). In addition, more than 60% had never received any of the preventive measures evaluated, except for the blood pressure assessment. In the adjusted model, people with ADL disability had 63% less probability of having extensive insurance, compared to those without disability (p<0.05). Conclusions This study shows that this Peruvian older population living in extreme poverty has limited access to healthcare services. Although there was no consistent association between ADL disability and the healthcare access, there is an urgent need to reduce the inequitable access to healthcare of this poor Peruvian older population.